Reusable and Flexible Heterogeneous Catalyst for Reduction of TNT by Pd Nanocube Decorated ZnO Nanolayers onto Electrospun Polymeric Nanofibers - Arslan, Osman; Eren, Hamit; Bıyıklı, Necmi; Uyar, Tamer; Arslan, Osman (WILEY-V C H VERLAG GMBH, 2017)
An effective method for the fabrication of well designed nanocomposite for the catalytic reduction of 2,4,6-trinitrotoluene (TNT) was developed. Here, cubic palladium (Pd) nanoparticles were utilized for enhancing the interface properties, attachment quality, catalytic yield and stability after the catalysis reactions. Ligand controlled facet growth by the Br- anions during thermal decomposition of the palladium-precursor resulted with cubic shaped average similar to 13nm palladium nanocubes (Pd NC). The anisotropic Pd NC were utilized to decorate the surface of the zinc oxide (ZnO) nanolayers deposited by atomic layer deposition (ALD) technique on the electrospun polyacrylonitrile (PAN) nanofibers. Due to the polymeric nature of the electrospun PAN nanofibers, Pd NC decorated nanoweb is highly flexible and has a high surface area. For the sustainable Pd NC decoration on the ZnO surfaces coated on PAN nanofibers, anchor points were formed by the functional thiol groups which can facilitate the Pd NC attachment and stability on the ZnO surface. The -OH and alkyl thiol groups obtained via sol-gel reactions positioned on the ZnO layer providing a better interface between ZnO and Pd NC which cannot be obtained by pristine PAN nanofibers. Additionally, due to the increased surface interaction, geometrical positioning on fibers for a better intermediate complex formation and stability via soft-soft interaction, Pd NC decorated flexible polymeric electrospun nanoweb provided enhanced catalytic reduction of TNT in aqueous medium.
WOS: 000412681900013
Keywords: ALD; Catalytic reduction; Electrospinning; Nanofibers; Palladium nanocubes; TNT